Additional Adverse Perinatal Outcomes With No Effect on Neonatal Mortality and Birth Defects in Pregnancies Conceived by Assisted Reproductive Technology - Xiong, Yingying; Zang, Xiaodong; Xie, Tingting; Yang, Chaolei; Jiang, Xiaohua; Chen, Mingwu (Frontiers in Pediatrics, 2022)
Background: The pregnancy outcomes and perinatal diseases of children born with assisted reproductive technology (ART) and spontaneous conception (SC) are still unclear. We sought to compare the effects of pregnancy by ART and pregnancy by SC on neonatal and perinatal outcomes. Methods: We included 5913 neonates admitted to the neonatal intensive care unit (NICU) in the First Affiliated Hospital of USTC from January 2017 to December 2020. There were 1112 (18.8%) ART pregnancies and 4801 (81.2%) SC pregnancies. Maternal characteristics, comorbidities during pregnancy, general newborn data and neonatal diseases were collected and analyzed. Results: The average maternal age, ratio of first delivery or cesarean section, and history of adverse pregnancy outcome in the ART group were higher than those in the SC group. The incidence of pregnancy-related complications in mothers receiving ART, such as gestational diabetes mellitus (GDM), gestational hypothyroidism, rheumatic immune diseases, and reproductive system diseases, was higher than that in the SC group. The newborns conceived from ART presented lower means of gestational age, weight, length, and head circumference at birth. The adverse perinatal outcomes of the newborns, such as preterm birth (adjusted odds ratio [AOR] = 4.80, 95% CI 3.96-5.80, p < 0.001), bronchopulmonary dysplasia (BPD) (AOR = 1.51, 95% CI 1.01-2.27, p = 0.045), and neonatal respiratory distress syndrome (NRDS) (AOR= 1.42, 95% CI 1.11-1.83, p = 0.005) were higher in the ART group than in the SC group. There were no significant differences between the two groups in terms of newborn birth defects or mortality. Conclusion: Compared with pregnancy by SC, more mothers who conceived by ART had previous reproductive system diseases, GDM, gestational hypothyroidism, and rheumatic immune diseases. Furthermore, more adverse perinatal outcomes such as BPD, NRDS and premature birth were observed in ART pregnancise. Therefore, women who conceive by ART must improve their perinatal health and management of pregnancy-related comorbidity to avoid premature birth.